Plasminogen and the Plasminogen Receptor, Plg-RKT, Regulate Macrophage Phenotypic, and Functional Changes - Vago, Juliana P.; Sugimoto, Michelle A.; Lima, Kátia M.; Negreiros-Lima, Graziele L.; Baik, Nagyung; Teixeira, Mauro M.; Perretti, Mauro; Parmer, Robert J.; Miles, Lindsey A.; Sousa, Lirlândia P. (Frontiers in Immunology, 2019)
Inflammation resolution is an active process that functions to restore tissue homeostasis. Clearance of apoptotic leukocytes by efferocytosis at inflammatory sites plays an important role in inflammation resolution and induces remarkable macrophage phenotypic and functional changes. Here, we investigated the effects of deletion of either plasminogen (Plg) or the Plg receptor, Plg-RKT, on the resolution of inflammation. In a murine model of pleurisy, the numbers of total mononuclear cells recruited to the pleural cavity were significantly decreased in both Plg-/- and Plg-RKT-/- mice, a response associated with decreased levels of the chemokine CCL2 in pleural exudates. Increased percentages of M1 macrophages were determined in pleural lavages of Plg-/- and Plg-RKT-/- mice without significant changes in M2 macrophage percentages. In vitro, Plg and plasmin (Pla) increased CD206/Arginase-1 expression and the levels of IL-10/TGF-β (M2 markers) and while decreasing IFN/LPS-induced M1 markers in murine bone-marrow-derived macrophages (BMDMs) and human macrophages. Furthermore, IL4-induced M2 polarization was defective in BMDMs from both Plg-/- and Plg-RKT-/- mice. Mechanistically, Plg and Pla induced transient STAT3 phosphorylation, which was decreased in Plg-/- and Plg-RKT-/- BMDMs after IL-4 or IL-10 stimulation. The extents of expression of CD206 and Annexin A1 (important for clearance of apoptotic cells) were reduced in Plg-/- and Plg-RKT-/- macrophage populations, which exhibited decreased phagocytosis of apoptotic neutrophils (efferocytosis) in vivo and in vitro. Taken together, these results suggest that Plg and its receptor, Plg-RKT, regulate macrophage polarization and efferocytosis, as key contributors to the resolution of inflammation.